Openness, technological changes and differentiation in Turkish manufacturing sector - (:unkn) unknown (Nova Science Publishers, Inc., 2012)
The literature frequently emphasizes the crucial role of manufacturing sector on the economic growth of developing countries. Regional distribution of manufacturing activities is one of the important dimensions of the issue. On the other hand, global integration, among others, has affected deeply the structural changes in manufacturing sector in the developing countries. However, this effect does not uniformly spread over country. One possible outcome of the global integration is the changes in the spatial distribution of the manufacturing sectors. The other is the change in the level of technology. By combining these two types of changes, the chapter analyzes the regional variations in the manufacturing activities during the period in which the Turkish economy has experienced a remarkable policy changes towards integration to the World economy through trade liberalization. © 2012 Nova Science Publishers, Inc. All rights reserved.